Regulations, Markets, Health : questioning current stakes of pharmaceuticals in Africa. Proceedings - (:unkn) unknown (My University, 2018)
This scientific meetings taked place in march the 26th to 29th 2018, in the city of Ouidah, Benin. Through this international colloquium, we have discussed the multiple stakes surrounding pharmaceuticals in Africa today, with particular consideration of their markets, the political and economic actors which they mobilize, related instruments of regulation, control and competition, modes of health care in which they are placed, and finally their modes of consumption by individuals, without losing sight of the adaptation of "traditional medicines" to the evolution of economic models. Regulation, with its broad sense of norms actually at play, legislative, biomedical, technical and commercial, seems to transverse these various questions and was thus be widely considered.
Keywords: African Research